Translation Shifts Of Verbs And Verb Phrases In Novel's Jodi Picoult: My Sister's Keeper Into Penyelamat Kakakku - Safitri, Rezkiana (2012)
This research studies the verbs and verb phrases innovel's Jodi Picoult: My Sister's Keeperinto Penyelamat Kakakku. The objectives of the study are to classify the translation shifts and to describe theequivalence of verbs and verb phrases in Novel's Jodi Picoult: My Sister's Keeper intoPenyelamat Kakakku. This research is a descriptive qualitative research. The data are texts containing sentences found in the data source whichis the translation shifts, especially verbs and verb phrases. The data source is the novel's jodi Picoult: My Sister's Keeperinto Penyelamat Kakakku. The data are analyzed by using dscribing method. The result of the study shows that, there are two translation shifts of verbs and verb phrases, namely; category shift and level shift. From 150 data found there are 6 translation shiftswhich belongs to category shifts, there are 29 data or 19%; verb is translated into noun, verb is translated into adverb, verb is translated into adjective, linking verb is translated into adverb, linking verb is translated into noun, and verb is not translated. There are 5 translation shifts belong to level shifts, there are 121 data or 81%; verb is translated into verb phrase, linking verb is translated into verb phrase, verb phrase is translated into noun, verb phrase is translated into verb, and verbphrase is translated into adjective. These percentage show that level is the most dominant. Secondly, the equivalence of translation divided into equivalencetranslation and non-equivalence translation. The equivalence translation is 147 data or 98% and non equivalence translation is 3 data or 27%. From these percentages, it can be concluded that the translation shifts of verbs and verb phrases in novel's Jodi Picoult: My Sister's Keeperinto Penyelamat Kakakkuis an equivalent translation.